Curvatures of the DIP Joints of the Hand. (December 2014) - Graham, Kraig S.; Goitz, Robert J.; Kaufmann, Robert A.
Background: The distal interphalangeal (DIP) joints of the hand are highly susceptible to osteoarthritis and trauma. Surgical treatment options mandate accurate characterization of their osseous anatomy; however, there are few studies that describe this. We describe the curvatures of the DIP joints by measuring the bone morphology using advanced imaging and modeling methods. Methods: The fingers of 16 right hand fresh frozen human cadavers were analyzed. Fingers showing signs of DIP joint arthritis were excluded. The fingers were scanned using microtomography (microCT). Measurements of the bony morphology were made using models created from the scans. Results: In each finger, there is no statistically significant difference between the radii of curvature of the ulnar and radial condyles of the middle phalanx head. Conversely, the radius of curvature of the distal phalanx ulnar groove is significantly greater than that of the radial groove. The radii of curvature of the groove of the distal phalanx and the condyles of the middle phalanx displayed nonconformity with disparity increasing from the index to small fingers. Remarkably, the radius of curvature of the distal phalanx central ridge and the mean radius of the middle phalanx condyles are essentially the same. Conclusion: The purpose of this study is to gain better insight into the DIP joints of the hand. The asymmetry between the distal phalanx grooves and the middle phalanx condyles suggests that there may be a translational component to DIP joint motion. Our understanding of morphology may lend insight into the biomechanics and disease progression within the DIP joints.